The Development and Challenges of Civil Law in Indonesia - Agustina, Ria; Anas, Kamal; Prayuti, Yuyut (IHSA Institute, 2025)
Civil law is a dynamic field that is constantly evolving in tandem with the evolution of human civilization, which is also impacted by technological advancements and global climate change. Civil law is fundamentally interconnected with the reinforcement of the internal supervisory function, which replaces the external supervisory function. This research aims to ascertain the current state of civil law and the obstacles it faces. The data was analyzed qualitatively, and the method employed normative juridical with secondary data. The findings indicate that the development of modern civil law is a direct result of its fundamental relationship with the relationship between government and society, which enhances the role and participation of society in various domains. Some of the modernizations of civil law that have emerged and are being used to strengthen internal functions related to external control are contract law, consumer protection law, and employment law.